AN AGGRESSIVE CATECHOLAMINESECRETING GLOMUS PARAGANGLIOMA: A CASE REPORT - Jasmiad, Nurbadriah; Ismail, Ilham; Shudim, Saiful Shahrizal; See, Chee Keong (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Head and neck paragangliomas (HNPGLs) are commonly detected at the carotid artery bifurcation and carotid body but may arise in the middle ear. HNPGL presents as slowgrowing, painless neck mass. Majority are non-functional with approximately 5% being biochemically active. HNPGLs are generally locally invasive, and destructive and up to 19% may be malignant. Management for this type of paraganglioma is difficult and requires a multidisciplinary approach. We present a patient with a huge and locally aggressive functioning left glomus-jugulotympanicumparaganglioma with significant management challenges. CASE A 33-year-old male presented with left ear pulsatile tinnitus which was treated as left otitis media. Despite the persistent symptoms and progressive hearing impairment in the left ear, an investigation for suspicion of glomus tympanicum commenced 6 months later. He had repeated ER visits for the next year due to the persistence of symptoms and uncontrolled hypertension. However, he was only referred to the endocrine clinic for young hypertension investigation 20 months from the initial presentation with significant paroxysms of palpitation, headaches and elevated BP. Diagnosis of catecholaminesecreting glomus-jugulotympanicum-paraganglioma was confirmed with elevated urinary metanephrine and huge soft tissue mass in the left jugular fossa with local bony erosion and intracranial extension on MRI. His BP control was labile and required multiple oralantihypertensives including phenoxybenzamine. Multidisciplinary team management prepared him for definitive surgical intervention. He underwent tumour embolization prior to the actual surgery. Pre-operative management was extremely challenging which required CCU admission for BP stabilization. Intra-operative period was surprisingly uneventful, but he developed multiple cranial nerve palsies postoperatively. A second operation was required due to infection and enlarging tumor with compression. Paroxysm of symptoms improved after second surgery but he still had significant residual tumor. MIBG-therapy was planned but management was delayed due to the COVID-19 pandemic and treatment funding. CONCLUSION Awareness of functional paraganglioma presentation is imperative to avoid late detection. HNPGLs that are both aggressive and functional pose extreme difficulty in achieving disease remission.